The Duties Of Controlling Shareholders: The Agenda For Reform - Salim, Mohammad Rizal (Journal of Malaysian and Comparative Law, 1999)
The purpose of this article is to trace the development of the law relating to the duties of controlling shareholders and discuss whether there are justifications in the Committee's proposals for reform in this area.